The use of computer technologies at an assessment of sensory-motor reactions in single combats - Volodymyr Ashanin; Vyacheslav Romanenko (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to develop a complex of program applications by an assessment of sensory-motor reactions of sportsmen who are engaged in different types of single combats. Material and Methods: theoretical analysis and generalization of scientific and methodical literature, method of computer programming. Results: the computer program applications by an assessment of sensory-motor reactions of sportsmen-wrestlers are developed and the preliminary approbation of appendices is carried out, their metrological informational content is confirmed. Conclusions: during the approbation the received results confirm the data on characteristic values of the level of psychomotor reactions of sportsmen which are available in literature. It allows recommending the developed computer applications for a practical use